(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2023)
Among the causes of the prevalence of obesity and overweight in the population is the lack of physical activity. According to WHO data, more than 80% of adolescents in the world have an insufficient level of physical activity. Objective: To analyze and compare the levels of physical activity, physical condition and BMI of eighth grade and first middle school students of a school in the city of Talca. Methods: We evaluated 136 students with an average age of 13.6 years old. Sociodemographic data were established, physical activity and physical condition levels were evaluated by means of evaluations and self-report tests. Results: No significant differences were found in BMI between males and females (22.3±2.7 vs. 21.2±4.8, p=0.17). There was a low mean of 4.48±1.1 of physical activity, women presented a lower score (4.14±1.09) compared to men (4.85±1.05) (p<0.001). In physical condition with respect to sexes, significant differences were found in all the variables evaluated, being higher in men, based on the differences in hours of physical education, lower scores of physical activity were seen in students of eighth grade (4.42±1.09), compared to first middle school (4.6±1.17) with respect to physical condition, statistical differences were found between courses, being students of first middle school those who presented better results (p<0.05). Conclusions: The more hours of Physical Education per week, the higher the levels of physical activity. The results indicate that students in first year show a better physical condition than students in eighth grade.